2009
DOI: 10.1590/s0100-204x2009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Atributos físicos, químicos e biológicos de um Latossolo de cerrado em plantio de espécies florestais

Abstract: Resumo -O objetivo deste trabalho foi avaliar o impacto de plantios fl orestais nos atributos físicos, químicos e biológicos de um Latossolo Vermelho-Amarelo de cerrado. Amostras de solo foram coletadas à profundidade de 0 a 10 cm, em áreas cultivadas há mais de 20 anos com pínus (Pinus tecunumanii), eucalipto (Eucalyptus grandis) ou carvoeiro (Sclerolobium paniculatum). Uma área adjacente de cerrado nativo foi incluída como referência do solo original. Foram observados, em relação ao cerrado, aumentos na dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
1
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
8
16
1
12
Order By: Relevance
“…This was also observed by Cardoso et al (2011) in an area of grazing land converted from woody vegetation; by Liu et al (2002) who studied the effect of natural forest, grassland, shrub, secondary forest as forest on soil properties; and by Silva et al (2009) who studied the attributes of a Cerrado Oxisol planted with forest species. According to Gama-Rodrigues et al (2008a), the non-variability of P available in soils under different types of vegetation is associated with the robust stabilization of this element in highly weathered soils.…”
Section: Results End Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This was also observed by Cardoso et al (2011) in an area of grazing land converted from woody vegetation; by Liu et al (2002) who studied the effect of natural forest, grassland, shrub, secondary forest as forest on soil properties; and by Silva et al (2009) who studied the attributes of a Cerrado Oxisol planted with forest species. According to Gama-Rodrigues et al (2008a), the non-variability of P available in soils under different types of vegetation is associated with the robust stabilization of this element in highly weathered soils.…”
Section: Results End Discussionsupporting
confidence: 66%
“…Studies with chronosequences of forest to pasture areas in the Amazonia region have shown that the microbial biomass reduced in the soil after three years of establishment of pastures (CENCIANI et al, 2011) and change in the composition of the microbial community (LAMMEL et al, 2015). Similar results were also observed by Silva et al (2009) who reported that MB-C under managed forest was about half of that found under Cerrado. Changes in MB are connected to components of the vegetation, in particular diversity.…”
Section: Results End Discussionsupporting
confidence: 53%
“…The MBC indicates changes in the soil ecosystem balance (Baretta et al, 2005(Baretta et al, , 2008Silva et al, 2009;Baretta et al, 2010;Kaschuk et al, 2010). The MBC values found in this study were almost double those reported by Baretta (2007) and Bertini (2010) and are within the range of values found by Carvalho et al (2012) in soils under native and reforested Araucaria forests in the State of São Paulo, and within the range found for ecosystems of Atlantic forest (683 -1520 mg C kg -1 soil) (Kaschuk et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Além dos efeitos associados à remoção da vegetação nativa e intensidade de manejo do solo, as reduções no Cmic, possivelmente, também refletiram alterações associadas à quantidade e à qualidade dos resíduos vegetais disponíveis à microbiota (Gama-Rodrigues et al, 2008;Silva et al, 2009). Isso ficou mais evidente principalmente no sistema CCE, que, apesar de ausência de manejo do solo após o plantio do eucalipto, ainda apresentou Cmic significativamente inferior ao do CN, notadamente na profundidade de 0-10 cm (Quadro 3).…”
Section: Resultsunclassified